Nonprobative photos rapidly lead people to believe claims about their own (and other people's) pasts. - Cardwell, Brittany; Henkel, Linda; Garry, Maryanne; Newman, Eryn; Foster, Jeffrey (Memory & Cognition, 2016)
Photos lead people to believe that both true and false events have happened to them, even when those photos provide no evidence that the events occurred. Research has shown that these nonprobative photos increase false beliefs when combined with misleading suggestions and repeated exposure to the photo or target event. We propose that photos exert similar effects without those factors, and test that proposition in five experiments. In Experiment 1, people saw the names of several animals and pretended to give food to or take food from each. Then people saw the animal names again, half with a photo of the animal and half alone, and decided whether they had an experience with each. The photos led people to believe they had experiences with the animals. Moreover, Experiments 2-5 provided evidence that photos exerted these effects by making it easier to bring related thoughts and images to mind-a feeling that people mistook as evidence of genuine experience. In each experiment, photos led people to believe positive claims about the past (but not negative claims), consistent with evidence that feelings of ease selectively increase positive judgments. Experiment 4 also showed that photos (like other manipulations of ease) bias people's judgments broadly, producing false beliefs about other people's pasts. Finally, in Experiment 5, photos exerted more powerful effects when they depicted unfamiliar animals, and thus could most help bring information to mind. These findings suggest that nonprobative photos can distort the past without other factors that encourage false beliefs, and that they operate by helping related thoughts and images come to mind.